Becoming Comfortable with MY Epilepsy: - Naomi Elliott (Grounded Theory Review: An International Journal)
This short paper on Becoming comfortable with MY epilepsy is part of the How2tell study on disclosure and epilepsy. The purpose of the study is to explain how people with epilepsy (PWE) disclose information about their condition and, using this knowledge, develop a multi-media educational resource that will support PWE learn how to tell other people about their epilepsy. The inductive approach of grounded theory (Glaser, 1998) allow for a viable means to generate a robust explanation about disclosure—one that was grounded in the realities of PWE everyday life. From a healthcare and policy perspective (England, Liverman, Schultz, & Strawbridge, 2012), providing access to relevant and usable knowledge for people with epilepsy that meets their individual needs is important to enable them to participate effectively in self-care management. Grounded theory, therefore, was essential to the How2tell study, which was successfully awarded a research grant from the highly competitive Health Research Board and Epilepsy Ireland’s research grant programme.